Determination of ageing properties of Turkish stones and investigation the effectiveness of diammonium phosphate consolidant - Çelik, Selen Ezgi (My University, 2021)
Conservation of built heritage is an important subject for both culturally and scientifically. Stone, as the dominant component of the structures, has the major importance among the materials. There has been a great interest and research on stone conservation for decades. However, for being a natural resource, there are hundreds of different stone types used in cultural heritage sites and each site should have been treated individually because of that uniqueness. In this study, different types of Turkish stones (Ankara, Bitlis, Mardin and Nevsehir) have been investigated. They have been chosen for being not only important for geoheritage of Anatolia, but also a construction material for valuable architectural heritage. In the first part of the study, manual weathering cycles (frost-thaw and thermal degradation) have been applied. Thermal degradation experiment plan has been created by using Design Expert 7.0 software. The results have been compared with automated ageing cycles that took place in the weathering cabinet. In the second part of the study, DAP (Diammonium Phosphate) treatment has been applied on raw samples and effectiveness of the consolidant have been evaluated by analyzing surface hardness, surface roughness, ultrasonic pulse velocity, drilling resistance, color and hydric properties. As the last part of the study, a soft capping (plant covering) simulation has been performed on Mardin and Nevsehir stones. The data of temperature difference has been collected and results have been analyzed by comparing the samples.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2021
Keywords: Cultural heritage; Consolidant treatment; Deterioration mechanisms of stone; Accelerated aging studies